Impact of Communication Skills Courses on Student Engagement in Social Media Platforms - Alsolami, Ahmad (Journal of Posthumanism, 2025)
This study examines the impact of a communication skills course on students' engagement with social media platforms. Analysing pre- and post-questionnaire replies reveals substantial alterations in students' behaviours, confidence, and beliefs about communication skills. The findings demonstrate that formal communication training enhances social media engagement in active participation, audience awareness, and content creation. This quantitative study provides significant insights into integrating communication skills education with digital engagement tactics. This study highlights the significance of structured communication education in improving digital literacy through comprehensive statistical analysis and an expanded contextual framework.